The Origins of the Non-Refoulement Principle and Refugee Admission Considerations in the Refugee Protection Framework - Heribertus Untung Setyardi (Jurnal Kewarganegaraan, 2023)
Abstract The principle of non-refoulement is the backbone of international refugee protection. This principle is often used as a foundation for refugees in the hope that the countries to which refugees come can accept and provide protection for them. However, there are still attitudes and legal products from countries that are not in line with the purpose of this non-refoulement principle. This is believed to be due to countries' lack of understanding of the principle. In this regard, this article will discuss the origins of the regulation of the principle of non-refoulement, such as the main idea that gave rise to the international refugee protection regime. In addition, this article will also provide some insights that can be taken into consideration for a country to accept refugees in its territory. The aim is that countries can have a full understanding of why refugees need to be given protection, and what can be done to overcome refugee problems. Keywords: Non-Refoulement, Refugee Protection, Refugee Admission.